Tinjauan Yuridis Terhadap Gugatan Kabur (Obscuur Libel) Dalam Kasus Wanprestasi Penanaman Modal Usaha Pada PT Arasy Mulia Utama - Zahid Nugrah Arafah; Robi Syafwar (CV. ITTC INDONESIA, 2024)
The research in this thesis is based on decision Number 110/Pdt.G/2020/PN.Pdg in which ade frinando as the plaintiff sued maryati zamsya for default in a business capital investment case where on August 6, 2018 the plaintiff and the defendant agreed to enter into a business capital agreement the parties agreed that the second party would receive a dividend of around 2 percent (2 percent) of the profit every semester during the agreed period of 2 ½ years After 6 months since the capital was invested there has been no distribution of results so that the defendant demands that the plaintiff return the capital that the defendant has invested on this basis the plaintiff sues the defendant for default. The problem formulation of this thesis is (1) what are the considerations of the judge in deciding the case in decision number 110/pdt.G/2020/PN.pdg (2) what are the legal consequences for both parties to decision number 110/Pdt.G/2020/PN.Pdg. In this study, the type of research used by the author is normative legal research, the type of research used by the author is descriptive, the author's data collection source uses literature study techniques and document studies The analysis used in this study uses qualitative analysis methods. He results showed that (1) The reason why the plaintiff sued the defendant was because of the default of the agreed business investment on the date on which the defendant withdrew the capital before the agreed time (2) The reason why the defendant withdrew the capital was because there was no profit sharing between the two parties (3) The judge accepted the defendant's exception regarding the obscure lawsuit (obscuur libel) by declaring the plaintiff's lawsuit unacceptable (Niet Ontvantkelijk Verklaark)